Відображення інтелектуалізації української мови кінця ХІХ ст. в оповіданнях Агатангела Кримського - Голоюх, Л. (Культура слова, 2021)
Статтю присвячено проблемі інтелектуалізації української літературної мови у зв’язку з художньо-естетичною традицією кінця ХІХ ст. На матеріалі мови оповідань Агатангела Кримського простежено функціонування книжної лексики – термінів, лексичних одиниць абстрактної семантики. Встановлено стилістичні функції лексико-тематичних груп: «мова» – назви мов, мисленнєво-мовленнєвих процесів, лінгвістичних понять орієнталістики, назв соціальних типів мови; «освіта» – назви осіб, предметів, професій; «культура і мистецтво» – власні і загальні назви, поняття літературознавства; «суспільно-політичне життя». Акцентовано увагу на лінгвософії автора, мовний світ якого вмістив наукові, мистецькі, естетичні, світоглядні, морально-етичні аспекти українського суспільства кінця ХІХ – початку ХХ століття. Визначено вплив наукового інтелекту й лінгвістичної ерудиції Агатангела Кримського на формування лексичного ядра його прозових текстів. This article is dedicated to the linguo-cognitive comprehension of the intellectual sphere of language markers in the short stories of Ahatanhel Krymskyi. The author studies the function of scientific notions and language units of abstract semantics. The author studies lexical-semantical language field- the names of languages, thoughtlanguage processes, linguistic notions of orientalistics. The light is shed on the linguo-pragmatical personal names which reflect the political structure of the state, the level of science, education, culture, as well as the names of the educational purpose as the national space dominants whichprovide the local coloring to the described events, personal names of different famous people of different historical periods: politicians, philosophers, writers, composers, names of characters, names of fictional and scientific works as well as the notions and phenomenon connected to the famous people. The author studies nominations that reflect cultural and political life in Ukraine of the end of XIX century: ukrainophilism, liberalism, awareness and such, pragmatics of choosing not to transliterate Latin, French and Italian expressions. The author highlights Krymskyi’s linguosophy, who’s language universe contained scientific, artistic, esthetical, existential, moral and ethical aspects of the Ukrainian society in the end of XIX, the beginning of XX century. Ahatanhel Krymskyi’s intellect and his scientific erudition impacted the shaping of the lexical core of his prose.